When reality bites: What draws us to true crime? - United Nations Educational, Scientific; Cultural Organization; Rachel Franks (The UNESCO Courier, 2025)
Borrowing narrative elements from both investigative journalism and the crime novel, true crime – often called “crime documentary” – has long fascinated the public. Today, streaming series and podcasts are putting a huge boost on this deeply rooted popular culture genre. Its success stems partly from a human need to comprehend the inexplicable, confront our fears, and draw a clear line between good and evil. However, these criminal narratives also bring significant ethical questions to the forefront.